Pengaruh Waktu Kontak Air Jeruk Nipis (Citrus aurantifolia Swingle) Terhadap Peningkatan Kualitas Kebersihan Piring - Puja Krisnawati; Isnawati Isnawati; Darmiah Darmiah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Influence Of Contact Time Of Lime Juice (Citrus aurantifolia Swingle) On Improving The Quality Of Plate Hygiene. Equipment potential as food contamination is not clean enough and not appropriate washing process, because skip disinfection stage. One of disinfection process is by giving lime juice (Citrus aurantifolia Swingle)10%. The purpose of this study was to determine the effectiveness of contact time of lime juice (Citrus aurantifolia Swingle) on improving the quality of plate hygiene. This study used experimental methode, data analysis was using Paired Sample T-Test and One Way Anova. The data was obtained by trial soaking plate in lime juice (Citrus aurantifolia Swingle) 10% at contact time 1, 1,5 and 2 minutes. The result laboratory that the number of germs post-treatment was smaller than pre-treatment. E. coli on pre-treatment and post-treatment was negative. The contact time at 2 minutes could reduce the number of germs of 89,48%. The Effective time on reduce the number of germs is 2 minutes and have qualify. It is suggested to the public to do the disinfection process by lime juice at least 2 minutes. To facilitate the use in the community researcher further can make concentration controller of lime juice 10%.